Human Resource Development, Education, and Human Development Index Disparities in Peru - Cordova, Nancy V. Quispe; Estrada, Betzabeth B. Huamán; Condori, Cledi Puma; Choque, Yuli P. Mamani; Areche, Franklin Ore (The Indonesian Institute of Science and Technology Research, 2026)
Human Resource Development (HRD) plays a fundamental role in shaping national competitiveness, social equity, and sustainable development, particularly in developing countries. In Peru, disparities in the Human Development Index (HDI) across regions highlight persistent structural inequalities in education, skills development, and institutional capacity. This opinion-based article argues that education-centered HRD represents the most strategic lever for reducing HDI disparities and strengthening national development. Drawing on global and regional literature, the article proposes a conceptual framework linking education quality, HRD investment, human capital formation, and regional HDI outcomes. The analysis identifies three core challenges: unequal education access and quality, structural inequalities in HRD policy implementation, and regional economic disparities affecting human capital outcomes. The article also situates Peru within the broader Latin American context, demonstrating similarities in structural constraints and policy opportunities. The findings suggest that transformative HRD strategies must integrate educational reform, institutional strengthening, and equitable regional investment. Without a systemic HRD approach grounded in education equity, Peru risks reinforcing regional disparities and limiting its global competitiveness. This article contributes to policy discourse by proposing education-driven HRD as the foundation for equitable human development and long-term national resilience.